Antibacterial Activity of Ethanolic Extract of Kitolod (Hippobromalongiflora) Leaf Against Staphylococcus aureus and Salmonella typhi - Anjelina, Simanjuntak Helen (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study was to determine at what concentration of ethanol extract of kitolod leaves is active against Staphylococcus aureus and Salmonella typhi. Methods: Ethanolic extract of Kitolod leaves was tested for phytochemical screening by using standard protocol. Antibacterial testing was using the diffusion disc method to measure the inhibition zone against the Staphylococcus aureus and Salmonella typhi with various concentration of Kitolod leaves extract (6.25%, 12.5%, 25%, 50%, and 75%). Results: Phytochemical screening showed that ethanolic extract of Kitolod leaves contain alkaloids, flavonoids and saponins. The antibacterial inhibition of ethanol extract of kitolod leaves against Staphylococcus aureus and Salmonella typhi bacteria at a concentration of 75% had a diameter of 11.3 mm and 12.16 mm with a strong category. Conclusions: Kitolod leaf could be use as a novel antibacterial agent.